Effectiveness of One Minute Preceptor Model of Teaching, in Ophthalmology Students ofMohtarma Benazir Bhutto Shaheed Medical College, Mirpur, Azad Jammu Kashmir - Khan, Waseem Ahmed; Khaliq, Tanwir (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate effectiveness of one minute preceptor Model of Teaching in Ophthalmology students in MBBS, MC, Mirpur, AJK.Study Design: Cross-sectional Study.Place and Duration of Study: Mohtarma Benazir Bhutto Shaheed Medical College, Mirpur, AJK , Pakistan, from Oct 2019- Sep 2021. Methodology: After permission from RERC, sampling was done by Census method, Non-Probability convenience sampling. An orientation session about one minute preceptor Model of teaching was held, so that students can understand its methodology. The students were exposed to OMP Model in OPD clinical classes, after which a questionnaire comprised of 12 closed ended questions was filled by students to check effectiveness of one minute Preceptor Model. Results: The survey questionnaire comprised of 12 questions, it was filled by 100 students to check effectiveness of one minute preceptor. So, a total of 1200 responses to various aspects of one minute preceptor model were obtained. Around 722(60.16%) strongly agreed with the questions, 236(19.66%) agreed, 21(1.75%) remained neutral, disagreed with the questions, 18(01.50%) slightly disagreed with the questions, 08(0.66%) strongly disagreed about effectiveness of one minute preceptor model. Maximum students strongly agreed upon one minute preceptor model facilitating Understanding treatment of disease 69(69%), followed by Case Presentation skills 66(66%) and Discussion of Diagnostic tests 66(66%).A statistically significant correlation was observed between “Assessment of history taking skills and “Making a spot diagnosis”,i-e p-value